2005
DOI: 10.1159/000088402
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E Regulates Primary Cultured Human Mesangial Cell Proliferation

Abstract: Background: The role of apolipoprotein (apo) E in kidney disease is still unclear. Animal studies have been performed, but it is doubtful if the conclusions are applicable to human beings. The objective of this study was to determine how apo E acts on human kidneys using primary cultured normal human mesangial cells (NHMCs) rather than animals used in previous studies. Methods: apo E and its isoforms E2, E3 and E4, or combinations with apo B were cocultured with primary NHMCs in serum-free medium. Premix WST-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…19 Investigators reported that the apoE took a protective role for kidney. 3,4 Some other investigations found that the apoE expression in renal glomerulus was elevated when compared with that of the normal group; 5-7 however, those studies did not explore the relation between apoE and Col-IV, FN, TGF-b1, and a-SMA. The deposition of lipids in glomeruli, as an important pathogenetic factor, involves in glomerular sclerosis and leads to progression of renal disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19 Investigators reported that the apoE took a protective role for kidney. 3,4 Some other investigations found that the apoE expression in renal glomerulus was elevated when compared with that of the normal group; 5-7 however, those studies did not explore the relation between apoE and Col-IV, FN, TGF-b1, and a-SMA. The deposition of lipids in glomeruli, as an important pathogenetic factor, involves in glomerular sclerosis and leads to progression of renal disease.…”
Section: Discussionmentioning
confidence: 99%
“…The GSI was calculated according to the method of Raij et al 9 The severity of the lesions in a minimum of 40 glomeruli (range 40-80) in each specimen was examined, graded from 0 to 4 points in accordance with the percentage of morphological changes on each glomerulus (0 = 0%, 1 += 1-25%, 2 += 26-50%, 3 += 51-75%, 4 += 76-100%). The number of glomeruli showing a lesion of 0 was n 0 , of 1+ was n 1 , of 2+ was n 2 , of 3+ was n 3 , of 4+ was n 4 . Forty (range 40-80) glomeruli were examined independently, and the average score of each specimen was then calculated.…”
Section: Renal Morphologymentioning
confidence: 98%
See 1 more Smart Citation
“…Elevated levels of albumin in urine serve as clinical predictors of diabetic nephropathy [42]. Apolipoprotein E modulates human mesangial cell proliferation depending on the length of stimulation and cell conditions [43]. It has been shown that mice with increased hyperlipidemia in plasma have an increased progression of renal disease [44].…”
Section: Proinflammatory Effects Of C-peptide In Kidneysmentioning
confidence: 99%